INVESTIGATION NONLINEAR BEHAVIOR OF RADON GAS (222Rn) - Kamislioglu, Mirac; Kulahci, Fatih (Ieee, 2014)
For chaotic structure showed dynamic system chaos analysis are used phase space reconstruction, correlation dimension and maximum Lyapunov exponent method and such methods. Chaotic time series analysis method is benefit signal processing method for determine of nonlinear behavior of dynamic system. In this study, the methods explained for the chaotic analysis of the time series, which is obtained based on the discrete or continuous measurements of a variable. In this work, for dynamic system analysis, a time series occurred with radon (Rn-222 gas) concentration. Chaotic structure determine, the monitoring trajectory that is a quantitative analysis method and the qualitative analysis methods were used such as the Lyapunov exponent, correlation dimension and power spectrum analysis.
22nd IEEE Signal Processing and Communications Applications Conference (SIU) -- APR 23-25, 2014 -- Karadeniz Teknik Univ, Trabzon, TURKEY
Keywords: Strange Attractors; Lyapunov Exponents